Shooting free throw: apakah dipengaruhi imagery dan keyakinan diri? - Fitri Agung Nanda; Novriansyah Novriansyah; Muhammad Imam Rahmatullah; Candra Widiastuti; Sigit Dwi Andrianto (Journal Of Sport Education (JOPE), 2020)
Shooting free throw is one of the most important techniques and often influences the final result of a match because this shot is usually a shot given as a reward for an offense. The purpose of this study was to determine whether there is an interaction between imagery training and self-efficacy that affects the results of shooting free throw on basketball extracurricular. This study used an experimental method with a 2x2 factorial design. The study population was basketball extracurricular participants in Bantul Regency. The instrument measured the level of efficacy using the self-confidence questionnaire and the results of the free throw shooting using the free throw throw test adopted from Arianto B. Analysis of the data in this study used an analysis of variance (ANAVA) of two paths at a significant level α = 0.05. The results of the study showed that there was no interaction between imagery training and self-efficacy in the results of shooting free throw on basketball extracurricular, seen by the value of sig = 0.835> 0.05